Selected areas of health and health care utilization by immigrants living in the Czech Republic - Brabcová, Iva; Kajanová, Alena (Neuro endocrinology letters, 2015)
OBJECTIVE: This investigation examined to what extent a selected group of immigrants in the Czech Republic receive healthcare for primary prevention and inpatient care. A partial aim of the research was to confirm the connection between immigrant health and their social situation. METHODS: Using a quantitative study technique, 1,014 legally established immigrants (Vietnamese, Polish, Ukrainian, Russian, and Slovak) between 18-65 years of age were interviewed. The selection of respondents was conducted using purposive selection. The stratification of the group was determined by nationality, age, and gender. RESULTS: Long-term illnesses were found significantly more frequently among Ukrainian immigrants and less frequently among Vietnamese immigrants. About half of the respondents had visited a GP and dentist in the previous year and 11.5% of respondents had been hospitalized in inpatient departments. Most of the surveyed immigrants had public health insurance (77.9%), one-fifth had contractual health insurance (19.6%) and 2.5% did not have health insurance. In statistical terms, Vietnamese, Ukrainian, and Russian immigrants had commercial insurance more often than Polish and Slovak immigrants. The utilization of public health insurance and healthcare among immigrants grew significantly in correlation with length of residency. The use of GPs for preventive health care also grew in correlation with knowledge of the Czech language. We found that less than nine percent of immigrants reported needing hospitalization for an illness, but were not hospitalized. CONCLUSION: Currently, immigration represents one of the most burning and sensitive global challenges. The outcome of this research clearly shows that improving immigrant Czech language skills and giving all legally established immigrants access to Czech public health insurance are important steps needed to increase access to healthcare for immigrants in the Czech Republic.
Keywords: emigranti a imigranti; Humans; pacientův souhlas se zdravotní péčí; lidé středního věku; Emigrants and Immigrants; Female; mladý dospělý; dospělí; lidé; hospitalizace; Adult; zdravotní pojištění; ženské pohlaví; Hospitalization; Male; Middle Aged; Czech Republic; Insurance, Health; Patient Acceptance of Health Care; Young Adult; Česká republika; mužské pohlaví